Children of the consumption society: strategies of dialogue with the customer child - Schmidt, Saraí Patrícia (2015)
This paper analyzes the process of advertisement construction and the constitution of contemporary child identities, in a time in which children have become closely related to the consumption society. The analysis comprises three interviews with professionals working in advertising agencies. Considering contributions by Zygmunt Bauman (1999, 2001, 2008, 2009), Beatriz Sarlo (1997), Néstor García Canclini (2008) and Renato Ortiz (2007) as starting points, the study problematizes teachings provided by the media about childhood, which establish a cultural policy that has delineated what means to be a child in contemporaneity. The paper addresses the limits of persuasive strategies that have thought and treated children as a target market, in a time when consumption has become an imperative.